Improvement Master Data Management : Case Study Of The Directorate General Of The Religious Courts Of The Supreme Court Of The Republic Of Indonesia - Alfiandi, Rama; Ruldeviyani, Yova (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Implementation of Master Data Management (MDM) in an organization aims to help the process of consolidating and integrating various master data sources into one separate source of truth, as well as helping to overcome data complexity that occurs in the process of synchronizing, consolidating and cleaning data from redundancy. The main obstacle at DG Badilag is that data is spread across various systems, in different formats, and is not well integrated. The aim of this research is to improve master data management at the Directorate General of Badilag using MD3M which has an impact on a more transparent, efficient and just justice system . To improve master data management, it is necessary to measure the maturity level with use Master Data Management Maturity Model (MD3M) by Spruit and Pietzka. The results of the assessment show that the MDM maturity level at the Directorate General of Badilag is 0 with an implementation level of 73% (48 out of a total of 65) of implemented capabilities. From these results, recommendations were prepared to increase the maturity level of the Directorate General of Badilag to level 2 in the three designated focus areas, namely strengthening data management in all aspects, from data structure, data quality and data protection. DG Badilag already has awareness in master data management and can increase MDM maturity to a higher level by implementing capabilities that have not been implemented and implementing activities that have not been implemented.